The Relationship Of Intelligence Capital With Marketing intelligence And Its Impact On The Competitive Strategies - Ali, Muzaffar H.; Abdulah, Sami S.; Esmail, Gabriel A. (Humanities Journal of University of Zakho, 2016)
The Intelligence Capital & Marketing intelligence as an independent variable consists of Three dimensions:Human Capital,Structural Capital,Relational Capital&Customer Understanding, Understanding Marketing, and Competitors Intelligence, Competitive Strategies as a dependent variable consists of three dimensions: Focus strategy, Strategy Low Cost Leadarship and Differentiation strategy. To reach the objectives of the current research, the variables have been processed depending on Descriptive Analytical Approach, fifty seven (85) Bank Managers with long experience and knowledge in the field of banking and its work were selected, Questionnaire forms were distributed among them which was designed as a data collection and analyzing tool in the field side so as to know: The extent to which the research samples were understood the importance of Intelligence Capital& Marketing intelligence for their banks? Awareness level of the respondents towards the Relationship of Intelligence Capital& Marketing intelligence With Competitive Strategies used in the current research in strengthening the bank marketing strategies in the surveyed banks? To answer the above questions default models have been set on a number of fundamental hypotheses reflecting the nature of the correlation and impact between the dimensions of Intelligence Capital & Marketing intelligence and the , Competitive Strategies, using a combination of statistical methods to analyze and determine the results via SPSS-v-18. The research reached a set of conclusions based on the results, the most important: There is a strong positive correlation between the independent variable dimensions collectively/individually and dependent variable, it turned out that the Partnership dimension is the most powerful dimension in correlation with , Competitive Strategies. The presence of a strong positive impact of Intelligence Capital & Marketing intelligence dimensions collectively/individually on the , Competitive Strategies, it turned out that the Partnership dimension has the most impact in strengthening the , Competitive Strategies. The search is over with a set of proposals in line with the conclusions to strengthen the base of this vital sector.